PARP inhibitors: A review of the pharmacology, pharmacokinetics, and pharmacogenetics - Zeng, Yi; Arisa, Oluwatobi; Peer, Cody J; Fojo, Antonio; Figg, William D (Seminars in oncology, 2024)
PARP inhibitors have emerged as a promising class of anticancer agents approved for the treatment of ovarian, breast, prostate, and pancreatic cancer. These inhibitors target PARP enzymes involved in DNA repair pathways and exhibit remarkable efficacy in cancers with genetic deficiencies in the homologous recombination pathway responsible for mending DNA double-strand breaks. While all PARP inhibitors demonstrate potent and selective inhibition of PARP1 and PARP2, the key enzymes involved in DNA repair, each agent within the class possesses unique pharmacological profiles distinguishing them from one another. This review aims to comprehensively examine the properties of the entire PARP inhibitor class while emphasizing individual pharmacologic and pharmacokinetic distinctions that inform clinical recommendations. Currently, four agents, namely olaparib, rucaparib, niraparib, and talazoparib, have obtained approval in the United States and Europe. Olaparib, the first approved PARP inhibitor, has been extensively studied and is indicated for a wider range of cancer types. Niraparib and talazoparib, the more recent additions to the PARP inhibitor class, possess the longest half-lives and are formulated for convenient once-daily dosing, alleviating the pill burden for patients when compared to older agents. Moreover, talazoparib undergoes minimal hepatic metabolism, reducing the potential for drug-drug interactions. Notably, niraparib is the sole PARP inhibitor recommended for dose reduction in hepatically impaired populations, whereas talazoparib and olaparib should be dose reduced in renally impaired populations. The mechanisms underlying these dose adjustment recommendations are further explored in this review. Additionally, this review briefly covers veliparib, a PARP inhibitor under development, and two recently approved PARP inhibitors in China, fuzuloparib and pamiparib. Although significant progress has been made in understanding PARP inhibitors, there are several unanswered questions that remain, necessitating further research across a broader spectrum of cancer types within this evolving class of anticancer agents.